Arquivos pessoais e/na educação: passados reinscritos no presente - Chaves Vasconcelos, Maria Celi; Santos Cunha, Maria Teresa; Bittencourt Almeida, Doris; Ermel, Tatiane de Freitas; Vieira, Alboni Marisa Dudeque Pianovski (Revista Diálogo Educacional, 2022)
Não se aplica.